Evaluation of Suspected Autosomal Alport Syndrome Synonymous Variants. Issue 3 (31st March 2022) - Rossanti, Rini; Horinouchi, Tomoko; Yamamura, Tomohiko; Nagano, China; Sakakibara, Nana; Ishiko, Shinya; Aoto, Yuya; Kondo, Atsushi; Nagai, Sadayuki; Okada, Eri; Ishimori, Shingo; Nagase, Hiroaki; et al.
Key Points: Mutations registered in the database for autosomal Alport syndrome do not include synonymous variants. Certain synonymous variants can affect pre-mRNA splicing, and transcript analysis should be carried out to evaluate synonymous variants. Our in vivo and in vitro splicing assays showed that two of the four synonymous variants cause exon skipping. Visual Abstract: Abstract : Background: Alport syndrome is an inherited disorder characterized by progressive renal disease, variable sensorineural hearing loss, and ocular abnormalities. Although many pathogenic variants in COL4A3 and COL4A4 have been identified in patients with autosomal Alport syndrome, synonymous mutations in these genes have rarely been identified. Methods: We conducted in silico splicing analysis using Human Splicing Finder (HSF) and Alamut to predict splicing domain strength and disruption of the sites. Furthermore, we performed in vitro splicing assays using minigene constructs and mRNA analysis of patient samples to determine the pathogenicity of four synonymous variants detected in four patients with suspected autosomal dominant Alport syndrome ( COL4A3 [c.693G>A (p.Val231=)] and COL4A4 [c.1353C>T (p.Gly451=), c.735G>A (p.Pro245=), and c.870G>A (p.Lys290=)]). Results: Both in vivo and in vitro splicing assays showed exon skipping in two out of the four synonymous variants identified (c.735G>A and c.870G>A in COL4A4 ). Prediction analysis of wild-type and mutated COL4A4 sequences using HSF and Alamut suggested these two variants may lead to the loss of binding sites for several splicing factors, e.g., in acceptor sites and exonic splicing enhancers. The other two variants did not induce aberrant splicing. Conclusions: This study highlights the pitfalls of classifying the functional consequences of variants by a simple approach. Certain synonymous variants, although they do not alter the amino acid sequence of the encoded protein, can dramatically affect pre-mRNA splicing, as shown in two of our patients. Our findings indicate that transcript analysis should be carried out to evaluate synonymous variants detected in patients with autosomal dominant Alport syndrome.